Ways of Social Inclusion and Integration of Children with Autism in Secondary Education, Inside and Outside the School Context, In the Region Thessaly - Konstantinos, Nikas; Gea, Esther Vega; Ortega-Tudela, Juana M. (Journal of Ecohumanism, 2024)
The aim of this study is to advocate the aggregate development of the future adults with autism, in terms of social integration. Thus, in order to study the autistic people’s course of development through the interaction between primary and secondary education, it focuses on school-based as well as out-of-school activities and interventions used by special education stuff in the Thessaly region. 99 people (mental health providers, trainers and relatives of people with autism) took part is the research, which combines qualitative and quantitative methods aiming to shed light on different perspectives of the issue. Early intervention, customized teaching methods and inclusive education seem to be of great significance, while the need for creating restricted programs and school-mental health services networks, along with a proper resource allocation play a significant role in the socialintegration of autistic people.